Chemical constituents and biological activities of Calophyllum venulosum Zoll. and Calophyllum inophyllum L. - Ismail, Ahmad Azri Fitri (2016)
A phytochemical investigation on the stem bark of two species from the Clusicaceae family, Calophyllum venulosum and Calophyllum inophyllum was carried out using various chromatographic techniques and xanthones, coumarin, terpenes and sterol were successfully isolated and identified. All of the secondary metabolites isolated were structurally characterized on the basis of modern spectroscopic evidence, such as 1D and 2D NMR, MS, IR and UV. Extensive chromatographic separations applied to the chloroform extract of the stem bark of Calophyllum venulosum resulted in one new xanthone; venuloxanthone, along with two other xanthones, caloxanthone I and tovopyrifolin C. The hexane extract afforded two pentacyclicterpenes; friedelin and lupeol. Meanwhile, purifications of the chloroform extract revealed the presence of a coumarin, benjaminin together with a xanthone, macluraxanthone. Two sterols, stigmasterol and β-sitosterol were also discovered to be present in the hexane extract. The crude extracts of both plants were screened for cytotoxic and antimicrobial activities. The cell lines used in the cytotoxic assays were human promyelocytic leukemia (HL60) and positive breast cancer (MCF7). For Calophyllum venulosum, only the methanol extract showed significant activity against MCF- 7, meanwhile the hexane and chloroform extracts from Calophyllum inophyllum were found to be active against both cell lines. The antimicrobial activities was carried out on Staphylococcus aureus S276, Bacillus subtilis B145, Staphylococcus epidermidis S273, Escherichia coli E266 and Serratia marcencens S381. From the tests, only the hexane and chloroform crude extracts from Calophyllum inophyllum showed weak inhibition against Bacillus subtilis B145, while no activity were indicated by the other crude extracts.